Freezing method assists calcium hypochlorite for synergistically promoting methane production from sludge anaerobic digestion. (15th December 2022) - Tang, Yujia; Chu, Shuangshuang; Su, Peixin; Guo, Ruichao; Duan, Yan; Wang, Yujie
Abstract: Anaerobic digestion is widely considered to be a promising technology for waste activated sludge (WAS) treatment, by which sludge stabilization and resource recovery are simultaneously achieved. The poor reaction efficiency however hinders the large-scale applications of WAS anaerobic digestion technology. This study reported an efficient sludge pretreatment method by combining freezing with calcium hypochlorite (Ca(ClO)2 ) for enhancing the anaerobic digestion efficiency. Experimental data showed that the optimal combination was freezing at −20 °C coupled with 0.075 g/g VSS (volatile suspended solids) Ca(ClO)2, by which the maximum biomethane production of 274.4 ± 8.2 mL/g VSS was realized, 1.62 times higher than that of the control. Model-based analysis demonstrated that higher potential and rate for methane production were attained by the combined pretreatment. Mechanism analysis revealed that the extracellular polymeric substances (EPS) and microbial cells were both effectively destructed when treated by combined freezing and Ca(ClO)2, and more dissolved organics were generated in consequence. Microbial analysis demonstrated that the co-treated reactor enriched more functional microbes (such as Methanosaeta, Methanosarcina and Candidatus_Methanofastidiosum ) responsible for biomethane generation than that of the control. Furthermore, the number of fecal coliform was largely reduced in co-treated reactor. As the correlation between sludge anaerobic digestion performance and numerous pretreatment parameters was systematically revealed, this study can provide important references for engineers when applying the combined freezing and Ca(ClO)2 technology in practical engineering. Graphical abstract: Image 1 Highlights: Combined pretreatment promoted anaerobic methane yield from sludge by 62.1%. SCOD concentration was increased by 15.2 times after combined pretreatment. The proportion of functional microbes reached 21.11% in co-treated digestor. Fecal coliform in digested sludge was largely inactivated by combined pretreatment.